calcule a expressão ( - 2 ) ^2 mais ( - 2 ) ^3
Soluções para a tarefa
Respondido por
0
Olá!
(-2)²+ (-2)³
4 + (-8)
-4
(-2)²+ (-2)³
4 + (-8)
-4
Respondido por
0
.
![(-2)^2+(-2)^3=4+(-8)=4-8=-4 (-2)^2+(-2)^3=4+(-8)=4-8=-4](https://tex.z-dn.net/?f=%28-2%29%5E2%2B%28-2%29%5E3%3D4%2B%28-8%29%3D4-8%3D-4)
base negativa expoente par = +
base negativa expoente ímpar = -
base negativa expoente par = +
base negativa expoente ímpar = -
Perguntas interessantes
Geografia,
11 meses atrás
Ed. Física,
11 meses atrás
Português,
11 meses atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás